DIY console table / Amirun Rafiq Khairul Anuar - Khairul Anuar, Amirun Rafiq (Faculty of Applied Sciences, 2019)
Transporting a fully assemble furniture is one of the difficulties faced by the consumers as it requires a huge amount of energy and space. It also can expose it to various form of harm. The implementation of Do It Yourself (DIY) concept will minimize energy and reduce the consumption of space needed during the transporting operation. An alternative raw material also need to be explored due to surplus source of solid wood. In this study, a DIY Console Table was designed and manufactured by using ,rubber wood panel. After undergoes design process and manufacturing process, a survey (using a set of questionnaires) was undertaken in evaluating the characteristics of the product based on gender and range of age. The characteristics that been evaluated were such as stability, suitability, DIY concept, handling, price and acceptance of consumers. A set of questionnaires was distributed to 100 correspondents. The results show that, there is no significant different for all characteristics of the product, except for suitability and price based on different gender. While, for range of age, there is a highly significant different obtained for the stability characteristic of product. There also no significant different for all characteristics of the product based on gender interaction with range of age. It can be concluded that the implementation of DIY concept on the product increased the efficiency of the product in terms of transporting, handling and space efficient